Pengembangan Media Pembelajaran Drag and Drop Titik Koordinat pada Bidang Kartesius Berbasis AI untuk Siswa Kelas VII MTs Yayasan Madrasah Islamiyah Sinaksak - Nadhira Eka Putri Prayudi; Nabila Mutiara Syifa; Putri Syahbilah; Fevi Rahmawati Suwanto (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to develop interactive learning media in the form of a drag-and-drop game of coordinate points on a Canva-based Cartesian plane to improve the understanding of Analytical Geometry concepts in grade VII students of MTs Yayasan Madrasah Islamiyah Sinaksak. This study applies the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation, and involves grade VII students in the odd semester of the 2024/2025 Academic Year as research subjects. Data collection instruments include expert validation sheets that assess aspects of material, language, and media design; student response questionnaires covering aspects of preferences, enthusiasm, willingness to learn, understanding, and motivation; and learning outcome tests in the form of pre-tests and post-tests. Feasibility analysis was carried out using a Likert scale, while media effectiveness was measured by comparing actual scores and ideal scores and improvements in learning outcomes were analyzed using the N-Gain formula. The results of the study indicate that the developed drag-and-drop media is categorized as feasible based on the validator's assessment, received a positive response from students, and is able to improve learning outcomes in the moderate to high category based on the N-Gain value. Thus, this media is declared effective and can be used as an innovative alternative in learning Cartesian coordinates at the MTs level.